An investigation of the magnetic carriers and demagnetization characteristics of the Gulang loess section, northwestern Chinese Loess Plateau. (30th April 2014) - Chen, Ting; Qiang, Xiaoke; Zhao, Hui; Sun, Youbin
Abstract We report the results of a rock magnetic and paleomagnetic investigation of unit L9 of the Gulang (GL) loess section, in the northwestern Chinese Loess Plateau (CLP). We demonstrate that the dominant magnetic remanence carriers are coarse‐grained pseudo single‐domain/multidomain magnetite particles, and hematite. The application of either thermal (THD) or alternating‐field demagnetization (AFD) yielded several normal polarity intervals interbedded with intervals of reversed polarity, but which cannot be correlated with standard geomagnetic polarity time scales. A greater number of normal polarity intervals, however, were evident after THD than after AFD. We propose that the normal polarities are either the result of overprinting of a viscous remanent magnetization (VRM) carried by coarse magnetite particles on the original depositional remanent magnetization (DRM); or that they represent genuine geomagnetic excursions (such as the Kamikatsura and Santa Rosa excursions) which are difficult to identify. In addition, we propose that in the case of the GL loess section, the effect of thermal demagnetization tails of a VRM is a possible reason why THD treatment yielded a greater number of normal polarity intervals than does AFD. However, reversed polarities obtained by either THD or AFD may be credible for sedimentary intervals with a relatively high content of hematite particles which preserve the primary DRM. Although numerous studies have proposed that THD provides more reliable paleomagnetic directions for loess sediments from the CLP, our results suggest that careful attention needs to be paid to the type of demagnetization method chosen, especially in the case of coarse‐grained loess deposits.